Reviews Left and Right: The Link Between Reviewers' Political Ideology and Online Review Language - Lorenz Graf-Vlachy; Tarun Goyal; Yannick Ouardi; Andreas König (Business & Information Systems Engineering, 2020)
Online reviews, i.e., evaluations of products and services posted on websites, are ubiquitous. Prior research observed substantial variance in the language of such online reviews and linked it to downstream consequences like perceived helpfulness. However, the understanding of why the language of reviews varies is limited. This is problematic because it might have vital implications for the design of IT systems and user interactions. To improve the understanding of online review language, the paper proposes that consumers' personality, as reflected in their political ideology, is a predictor of such online review language. Specifically, it is hypothesized that reviewers' political ideology as measured by degree of conservatism on a liberal–conservative spectrum is negatively related to review depth (the number of words and the number of arguments in a review), cognitively complex language in reviews, diversity of arguments, and positive valence in language. Support for these hypotheses is obtained through the analysis of a unique dataset that links a sample of online reviews to reviewers' political ideology as inferred from their online news consumption recorded in clickstream data.
Keywords: 000; Online consumer reviews; Political ideology; Review language; Reviewer personality